2016
DOI: 10.1074/jbc.m116.734517
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Odorant Receptor 51E2 in Human Melanocytes

Abstract: Olfactory receptors, which belong to the family of G-protein-coupled receptors, are found to be ectopically expressed in non-sensory tissues mediating a variety of cellular functions. In this study we detected the olfactory receptor OR51E2 at the transcript and the protein level in human epidermal melanocytes. Stimulation of primary melanocytes with the OR51E2 ligand β-ionone significantly inhibited melanocyte proliferation. Our results further showed that β-ionone stimulates melanogenesis and dendritogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(130 citation statements)
references
References 72 publications
2
128
0
Order By: Relevance
“…Interestingly, different oligomerization states can be observed for the same receptor also in other tissues. The OR51E1 paralogous olfactory receptor 51E2 was found as monomer in the prostate and in human pigment cells in a monomeric and dimeric form [33, 67]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, different oligomerization states can be observed for the same receptor also in other tissues. The OR51E1 paralogous olfactory receptor 51E2 was found as monomer in the prostate and in human pigment cells in a monomeric and dimeric form [33, 67]. …”
Section: Discussionmentioning
confidence: 99%
“…This study first uncovered the presence of an OR in the nuclear envelope. To date, the presence of an OR beyond the cytoplasmic membrane was only described for OR2A4, which is localized to the cytokinetic structures of HeLa cells, and for other ORs in the sperm, melanocytes, and brain (Zhang et al, 2012; Flegel et al, 2016; Gelis et al, 2016; Garcia-Esparcia et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…OR2AT4 is another example of the therapeutic potential of ORs in human skin because its activation promotes wound healing processes in human keratinocytes (Busse et al, 2014). They are also of major importance for the regulation of apoptosis, cytokinesis, hormone secretion and differentiation (Braun et al, 2007; Zhang et al, 2012; Maßberg et al, 2015; Gelis et al, 2016; Manteniotis et al, 2016a,b; Massberg et al, 2016; Tsai et al, 2016). However, the expression and localization of ORs in different areas of the brain, the spinal cord, the trigeminal (TG) and dorsal root ganglia (DRG) were recently described (Otaki et al, 2004; Garcia-Esparcia et al, 2013; Flegel et al, 2015; Goncalves et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was found that Olfr78 (the murine ortholog) responded to acetate and propionate, but not β-ionone(3). However, a study in 2016 did show evidence that β ionone is a functional ligand: this study demonstrated that cells natively expressing OR51E2 exhibited an increase in intracellular calcium in response to β ionone which was negated by transfection of siRNA for OR51E2 (27). In late 2015, it was reported that Olfr78 responded to lactate in addition to acetate and propionate(28), and this was confirmed by two other groups in 2016 (29, 30).…”
Section: Short Chain Fatty Acid Receptorsmentioning
confidence: 96%